Parental involvement in the lives of intercollegiate athletes - Parietti, Megan L; Sutherland, Sue; Pastore, Donna L (Journal of Amateur Sport, 2017)
Research has been growing on the topic of parental involvement in the lives of their children, and the concept of overinvolved parents. Little research has examined these topics in regards to intercollegiate student-athletes. This study addresses that gap by examining parental involvement in regards to intercollegiate student-athletes and their athletic and academic endeavors. Specifically it examines how involved parents are in the lives of their intercollegiate student-athlete children, and the concept of overinvolvement in regards to this population. A qualitative, case-study method was utilized for this research. Participants included eight intercollegiate student-athletes and the five academic advisors for athletics that worked with them. Participants completed two interviews and one journal, and all of the data was analyzed utilizing thematic analysis. The themes that emerged were types of involvement, increasing involvement, overinvolvement, outcomes of overinvolvement, and the fine line between healthy involvement and overinvolvement. The present study offers insight into how student-athletes and academic advisors perceive parental involvement. This knowledge can be utilized by practitioners to improve how they communicate with parents and student-athletes. Also, researchers can employ this information to improve the overall understanding of parental involvement in regards to athletes.